Optimalisasi Layanan Pelanggan dan Pemasaran Digital UMKM Handmade Depok - Khusni Faizah; Maylinda Nur Faizah; Felisya Pangi Wijaya; Meli Linda Sari; Mesja Dwika; Sultansyah Adira Putra; Suci Ayu Sudari; Udriyah; Ali Ridho; Nur Fitri Dewi; Alfi Maghfuriyah (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
The digital transformation era has significantly changed consumer behavior, demanding faster, more responsive, and accessible services. In response to these shifts, this community service program was conducted in the form of an educational seminar entitled "Optimizing Customer Service and Digital Marketing for Handmade MSMEs in Depok." This initiative aimed to enhance MSME actors’ understanding and skills in customer service and digital marketing through participatory methods combining lectures, interactive discussions, and practical training. The program was carried out by a team of management students at Jakarta Global University and involved selected handmade MSME participants. During the seminar, participants were equipped with knowledge about effective customer service strategies and the use of digital platforms such as Capcut, Instagram, and online marketplaces. The results showed increased participant awareness, improved ability to create promotional content, and readiness to apply digital marketing in their businesses. This initiative demonstrates the strategic role of higher education institutions in bridging theory and practice, while empowering MSMEs to become more competitive in the digital economy.